Limited long‐term treatment persistence of first anti‐TNF therapy in 538 patients with inflammatory bowel diseases: a 20‐year real‐world study. Issue 5 (20th June 2021) - Blesl, Andreas; Binder, Lukas; Högenauer, Christoph; Wenzl, Heimo; Borenich, Andrea; Pregartner, Gudrun; Berghold, Andrea; Mestel, Sigrid; Kump, Patrizia; Baumann‐Durchschein, Franziska; Petritsch, Wolfgang
Summary: Background: Anti‐TNF antibodies were the first biologic treatment option for patients with inflammatory bowel diseases. Aims: To assess length of treatment persistence of first anti‐TNF therapy and influencing factors used in the standard care of patients with inflammatory bowel diseases. Methods: Single‐centre, retrospective study from a register including patients who received anti‐TNF therapy in the last 20 years at the study centre. Kaplan‐Meier analysis with log‐rank test was used to describe treatment persistence. With multivariable Cox regression analysis, risk factors for treatment failure were investigated. Results: Five hundred thirty‐eight patients (CD, Crohn's disease: 367, UC, ulcerative colitis: 147, inflammatory bowel disease unclassified: 24) with a median follow‐up of 8.1 years were included. Median (95% confidence interval) treatment persistence in the total cohort was 2.3 years (28 [22, 38] months), and nearly half of patients withdrew from treatment within 2 years. Male patients were treated longer than females (male: 37 [25, 48] months, female: 23 [14, 33] months, P = 0.002). Treatment persistence was longer in CD compared to UC (CD: 39 [30, 50] months, UC: 13 [9, 19] months, P < 0.001), and patients with CD remained longer on adalimumab than on infliximab treatment (adalimumab: 67 [55, 95] months, infliximab: 19 [14, 31] months, P < 0.001). Treatment failure (52%) and side effects (25%) were the most common reasons for withdrawal from therapy; 14% withdrew due to remission. Female sex was identified as independent predictor for treatment failure in UC (hazard ratio [CI]: 1.73 [1.02‐2.92], P = 0.04). Conclusion: Long‐term treatment persistence of first anti‐TNF therapy was limited in patients with inflammatory bowel diseases, primarily due to treatment failure and side effects. Abstract : At the end of follow‐up, only 29% of patients still received scheduled treatment with the first anti‐TNF. Longer treatment persistence could be observed in males, in patients with Crohn's disease and for adalimumab treatment in Crohn's disease.